Reading Comprehension in Open High School Students: Effect of a Motivation Based Intervention and metacognitive strategies - Ruvalcabar-Estrada, Otoniel (2021)
The purpose of this study was to determine if there is a significant difference in the level of reading comprehension between a pretest and a posttest, in students of an open high school in Nuevo León (Mexico) after an intervention based on motivation and metacognitive strategies. A quasi-experimental quantitative design was used with an intervention of 14 weeks between the application of both measurements. The sample consisted of 18 students to whom three instruments were applied, the Cloze Test to measure reading comprehension, the Attributional Motivation Scale of General Achievement and the Inventory of General Metacognitive Strategies. The findings showed that there is a significant difference in reading comprehension (t (17) = 3.653, p = .002, Cohen'sd = 0.86) and metacognitive strategies (W = 30.00, p = .017, Biserial correlation r = 0.649) between the pretest and the posttest, although it was not significant in the level of motivation (t (17) = -0.341, p = .737, Cohen'sd = 0.008). In conclusion, through the execution of an intervention program in metacognitive strategies and motivation towards reading, an improvement in the level of reading comprehension of the participants was obtained.